Functional properties of Watermelon (Citrullus lanatus) and Pumpkin seed flours and protein isolate - Ikhlas Ibrahim Khalid (International Journal of Nutrition, 2023)
The current study was intended to evaluate the chemical composition, functional properties, of some cucurbits seed. watermelon (Citrullus lanatus), and Pumpkin (Cucurbita maxima), were studied. Proximate analysis gave 17.09% -17.07% protein, 35.55%-39.0% fat,6.00% - 5.5% total ash, 24.9%-2.6% crude fibre, and 10.60% - 28.83% carbohydrate, for Pumpkin and Watermelon seed flour respectively. The seeds are rich in protein, crude fat, and crude fiber. nutritional value in the seed can be recommended on daily allowance, maintenance of good nutritional status and good health. The functional properties of the seed revealed that water and oil absorption capacities for the seed were 3.20 - 5.60 (Ml/g) and 3.93 -3.50 (Ml/g) for Watermelon and Pumpkin seed flour respectively. Foam capacity and bulk density for the seed were 9.67 % -19.0 % and 0.77 (g/ml) -1.5(g/ml). for Pumpkin and Watermelon seed flour respectively. Water and fat absorption capacities, and foam capacity were fairly good in all seeds. However, Pumpkin seed flour gave good functional properties compare to watermelon seed flour. The oil of watermelon and Pumpkin are acceptable according to its chemical properties. The seeds contained high amounts of K, Mg, Na, P and Ca. The obtained results revealed that the seeds presented an alternative source of vegetable oil. Seeds could be added to food systems such as bakery products.
Keywords: watermelon